Colorblind injustice : minority voting rights and the undoing of the Second Reconstruction - Kousser, J. Morgan (Immigration law & policy in the U.S., 1999)
This book compares the failed First Reconstruction (after the Civil War) to the relatively successful Second Reconstruction, which encompasses the Civil Rights movement after World War II.